Membangun Loyalitas Pelanggan Berbasis E-Service Quality Dengan Mediasi Kepuasan Pelanggan (Studi pada Transportasi Online Grab-Car di Kota Medan) - Sari, Maya; Prayogi, Muhammad Andi; Jufrizen, Jufrizen; Nasution, Muhammad Irfan (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 14 Nomor 2 Tahun 2020DO - 10.24843/MATRIK:JMBK.2020.v14.i02.p07, 2020)
The purpose of this study was to analyze the effect of service quality on customer satisfaction, analyze the effect of service quality on customer loyalty, and analyze customer satisfaction on customer loyalty in Grab Online Transportation. This type of research is associative research, according to this associative, data tendencies are used in quantitative methods. This study uses 3 types of variables namely customer loyalty, satisfaction and quality of electronic services. The type of data used is primary data and secondary data. Data collection techniques used were interviews and questionnaires. The population of this study is the users of Grab online transportation services with the provisions that have used Grab transportation services more than twice. The sampling technique used was purposive sampling. For data analysis used Partial Least Square (PLS) based Structural Equation Modeling (SEM). The results of the study found that there was a positive and significant influence of e quality of service on Grab online transportation customer satisfaction, significant and significant positive contribution of e quality of service to Grab online transportation customer loyalty, and related positively and significantly of customer satisfaction to customer loyalty Grab online transportation.